Numerical Modeling and Simulation of Rooftop Thermal Photovoltaic Chimney for Buildings' Electrical Energy Generation and Passive Cooling - Nougbléga, Yawovi; Tchamie, Georges Kibalo; Ouedraogo, Seydou (International Journal of Membrane Science and Technology, 2023)
The present study consisted mainly of making the thermal and dynamic analysis of the fluid flows in mixed convection in the chimney integrated into the building with an upper-covered horizontal hybrid thermal photovoltaic collector on a slab roof. The governing equations discretized by the finite difference method resulted in the systems of tri-diagonal algebraic equations, which were solved by Thomas' algorithm and Gauss Seidel's iterative method. Numerical solutions are presented for various geometrical aspect ratios, Rayleigh, and Reynolds numbers. The results are presented in terms of streamlines, isotherms, velocity, heat transfer intensity, and PV cells’ electrical efficiency versus the governing control parameters in detail.